Bentuk Penyajian Kesenian Ronggiang di Jorong Rantau Panjang Kecamatan Sasak Ranah Pasisia - Yulia Mairoza; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2022)
Ronggiang is a traditional performing art found in the Sasak Ranah Pasisia community, West Pasaman Regency. The theoretical basis for the form of presentation from Djelantik. This type of qualitative research with descriptive analysis approach. Data collection techniques through observation, interviews, literature study and documentation. Data analysis is to classify primary and secondary data then arranged systematically and concluded. The results of the study are to describe the supporting elements of the Ronggiang performance such as: artists, musical instruments, songs, costumes/makeup, venues and audiences. So the form of presenting Ronggiang at a wedding ceremony is in the form of a performing arts of music, song, and dance as well as other elements in a single unit in traditional performances in the Sasak Ranah Pasisia community.